The Effect of Lactation Massage and Acupressure Therapy on Post-Part Mothers on Smooth Breast Milk Production - Kasmayani; Arnianti; Tahir, Dyah; Adeliana; Hamid, Hasnaini; Khatimah, Husnul (Jurnal Midwifery, 2026)
Introduction: Breast milk is the ideal natural source of nutrition for babies, meeting their energy and nutritional needs during the first 4-6 months of life. Furthermore, breast milk strengthens the emotional bond between mother and baby, which contributes to optimal growth and development. The aim of this study was to determine the effect of lactation massage and acupressure therapy on breast milk production in postpartum mothers. Method: This study used a quasi-experimental design with a one-group pretest-posttest design. The population was all postpartum mothers at the Solo Community Health Center (UPTD) during the October-November 2025 period, totaling 30 people. Therefore, a total sampling technique was used to select 30 people. Data collection was conducted using a questionnaire. The collected data were then processed and analyzed using the SPSS statistical program and the Wilcoxon test. Result: Based on the research results, the average score in the experimental group before giving lactation massage was 4.60 and after giving lactation massage was 6.40 and the difference in the range of breast milk production scores before and after giving acupressure massage was 1.80, which showed a significant change between the two variables. Conclusion : There is an influence of lactation massage and acupressure therapy on the smooth production of breast milk in postpartum mothers in the working area of ​​the Solo Health Center UPTD.